Carving a dialogical epistemology for investigating altruism: A reply to Mitchell and Eiroa–Orosa. Issue 4 (2nd October 2018) - Intezar, Hannah; Sullivan, Paul
ABSTRACT: This is a reply to Sue Mitchell and Francisco J. Eiroa-Orosa's 'Love your enemy.' The latter seeks to explore the self-transcending potential of altruistic behaviour through a dialogical paradigm. It not only initiates fresh discussion on the subject of altruism, but also advances new discussion on Bakhtinian aesthetics. For the continuation of this forward momentum, we suggest a more nuanced approach to the placement of the 'researcher' within the applied methodological matrix. Similarly, we also advocate for the synthesising of research tools, often appropriated by theological studies, into said methodological matrix. This is a reply to: Mitchell, Sue and Eiroa-Orosa, Francisco J. 2018. "Love your enemy? An aesthetic discourse analysis of self-transcendence in values-motivated altruism." Global Discourse https://doi.org/10.1080/23269995.2018.1511766